A comparative study of time-specific oxidative stress after acute myocardial infarction in patients with and without diabetes mellitus. Issue 1 (December 2016) - Kitano, Daisuke; Takayama, Tadateru; Nagashima, Koichi; Akabane, Masafumi; Okubo, Kimie; Hiro, Takafumi; Hirayama, Atsushi
Abstract Background Oxidative stress is involved in the initiation and progression of atherosclerosis, and hyperglycemia is known to increase oxidative stress, which injures the endothelium and accelerates atherosclerosis. To clarify the relation between oxidative stress, diabetes mellitus (DM), and acute myocardial infarction (AMI), we evaluated and compared time-specific oxidative stress after AMI in patients with and without DM by simple measurement of derivatives of reactive oxygen metabolites (d-ROMs) levels as indices of reactive oxygen species production. Methods Sixty-eight AMI patients were enrolled (34 non-DM patients and 34 DM patients). Using the FRAS4 free radical analytical system, we measured d-ROMs levels in each patient at two time points: 1 and 2 weeks after AMI onset. Results d-ROM levels decreased significantly between week 1 and week 2 (from 475.4 ± 119.4 U.CARR to 367.7 ± 87.9 U.CARR, p < 0.001) in the non-DM patients but did not change in the DM patients (from 463.1 ± 109.3 U.CARR to 461.7 ± 126.8 U.CARR, p = 0.819). Moreover, significant correlation was found in the total patient group between d-ROMs levels at 1 week and N-terminal prohormone of brain natriuretic peptide (r = 0.376, p = 0.041) and between d-ROM levels at 2 weeks and 2-hour oral glucose tolerance test glucose levels (r = 0.434, p < 0.001). Conclusions Exposure to oxidative stress is greater in AMI patients with DM than AMI patients without DM. Our study results suggest that it is the continuous hyperglycemia that increases oxidative stress in these patients, causing endothelial dysfunction and accelerating atherosclerosis. However, long-term follow up study is needed to assess whether the increased oxidative stress affects patient outcomes.